Promoting Tumor Accumulation of Anticancer Drugs by Hierarchical Carrying of Exogenous and Endogenous Vehicles. Issue 10 (19th August 2022) - Yue, Yu-Xin; Zhang, Zhanzhan; Wang, Ze-Han; Ma, Rong; Chen, Meng-Meng; Ding, Fei; Li, Hua-Bin; Li, Juan-Juan; Shi, Linqi; Liu, Yang; Guo, Dong-Sheng
Abstract : Promoting tumor accumulation of active pharmaceutical ingredients is crucial for targeted anticancer therapy. However, this issue has not yet been addressed because of the fast clearance or premature degradation, slow drug release kinetics, and nonspecific biodistribution of the reported formulations. Herein, a new drug delivery paradigm is proposed based on supramolecular hierarchical recognition to achieve high tumor accumulation of anticancer drugs by overcoming these three challenges. The prepared supramolecular ternary formulation of paclitaxel (PTX) contains two steps of molecular recognition: exogenous recognition of PTX by an artificial macrocyclic carrier, sulfonated azocalix[5]arene (SAC5A) in vitro, and endogenous recognition of PTX@SAC5A by intrinsic serum albumin in vivo. The ternary PTX@SAC5A⊂albumin concurrently accomplishes prolonged blood circulation, rapid drug release, and dual passive and hypoxia‐responsive targeting. As a result, the PTX@SAC5A⊂albumin formulation exhibits more efficient tumor accumulation than free PTX and albumin‐based, solvent‐based, liposome‐based, and sulfobutyl ether‐β‐cyclodextrin‐based PTX formulations, thereby contributing to better therapeutic efficacy. The current strategy paves the way for promoting the tumor accumulation of drugs, showing the advantages of simplicity, universality, and reproducibility. Abstract : The supramolecular formulation is formed by the hierarchical recognition strategy to achieve high tumor accumulation. The first recognition takes place by encapsulating paclitaxel into sulfonated azocalix[5]arene, and the second recognition takes place by hitchhiking the albumin in situ. This strategy paves the way for promoting the tumor accumulation of drugs, showing the advantages of simplicity, universality, and reproducibility.